Platelet-to-lymphocyte ratio as a biomarker of systemic inflammation in systemic lupus erythematosus: A meta-analysis and systematic review. - Young Ho Lee; Gwan Gyu Song (PLoS ONE)
Objective The objective of this study was to evaluate the relationship between the platelet-to-lymphocyte ratio (PLR) and systemic lupus erythematosus (SLE). Additionally, the study aimed to establish an association between PLR and SLE disease activity, specifically lupus nephritis (LN). Methods We conducted a comprehensive search across Medline, Embase, and Cochrane databases to identify relevant articles. Subsequently, we performed meta-analyses to compare PLR between SLE patients and controls, as well as active and inactive SLE cases, along with LN and non-LN groups. Furthermore, a meta-analysis was conducted on correlation coefficients between PLR and various parameters in SLE patients, including the SLE Disease Activity Index (SLEDAI), C3, C4, anti-dsDNA, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). Results In total, fifteen studies comprising 1,522 SLE patients and 1,424 controls were eligible for inclusion. The meta-analysis demonstrated a significant elevation of PLR in the SLE group compared to the control group (Standardized Mean Difference [SMD] = 0.604, 95% Confidence Interval [CI] = 0.299-0.909, p < 0.001). Upon stratification by ethnicity, an elevated PLR was observed in the SLE group among both Asian and Arab populations. Subgroup analysis based on sample size revealed consistently higher PLR in both small (n < 200) and large sample (n ≥ 200) SLE groups. Moreover, when considering disease activity, there was a noteworthy trend of increased PLR in the active disease group compared to the inactive group (SMD = 0.553, 95% CI = 0.000-1.106, p = 0.050). However, the meta-analysis did not demonstrate a significant distinction in PLR between the LN and non-LN groups. Notably, a positive association was established between PLR and SLEDAI (correlation coefficient = 0.325, 95% CI = 0.176-0.459, p < 0.001). Furthermore, PLR exhibited positive correlations with ESR, CRP, proteinuria, C3, and anti-dsDNA antibody levels. Conclusions The outcomes of this meta-analysis underscored the elevated PLR in SLE patients, suggesting its potential as a biomarker for gauging systemic inflammation in SLE. Additionally, PLR exhibited correlations with SLEDAI, as well as with key indicators such as ESR, CRP, proteinuria, C3, and anti-dsDNA antibody levels.